Define Intervention (The Biblical archaeology review, 2026)
What is a "hapax legomenon"? 1. A Roman curse 2. A Greek siege machine 3. A single-copy document 4. An AI-powered reading device 5. Any unique written word Answer: (5) Any unique written word Hapax legomenon (or hapax, for short) is a term used to refer to any written word that is unique. It can mean a word appears only […]